Tetraaquabis(biuret-κ2O,O′)yttrium(III) trichloride - William T. A. Harrison (Acta Crystallographica Section E, 2008)
In the title compound, [Y(C2H5N3O2)2(H2O)4]Cl3, the Y3+ ion (site symmetry 2) is bonded to eight O atoms (arising from two O,O′-bidentate biuret molecules and four water molecules) in a distorted square-antiprismatic arrangement. A network of N—H...O, N—H...Cl and O—H...Cl hydrogen bonds help to establish the packing, leading to a three-dimensional network. One of the chloride ions has site symmetry 2.